Fake Vaccine in Children and The Protection - Evie Fitriani (Journal La Sociale, 2020)
The development of vaccines in Indonesia is not only for adults but also for children. However, some of the vaccines for children in circulation are fake vaccines that do not provide the expected immune system. This study contains 2 problem formulations, namely: 1. Role of government. 2. Business actors' liability for losses suffered by consumers. This study used a statute approach and a conceptual approach. There are also other laws that regulate consumer protection laws regarding rights and obligations that are violated, the role of government in controlling these fake vaccines and its accountability.The result of this research is the role of government in deciding the distribution of fake vaccines in Indonesia as well as to fulfill consumer rights and business actors' responsibility for the distribution of fake vaccines and their compensation.